2018
DOI: 10.4103/sajc.sajc_105_18
|View full text |Cite
|
Sign up to set email alerts
|

Practical consensus recommendations for tumor margins and breast conservative surgery

Abstract: My suggestion: There is no difference in survival of breast cancer patients treated with either mastectomy or with breast conservation therapy combined with external beam radiotherapy. A positive margin (s) is an important factor contributing to the increased risk of local recurrence. However, in published literature, there is a lack of consensus on the definition of acceptable margin (s). As a result decision process about need for re-excision after positive margins remains uncrear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…To reduce the risk of LR, it is important to treat positive margins either by re-excision or mastectomy. 56 The RR rate in our study was 9.8%. This is comparable with the rate of re-excision reported by de la Cruz et al who conducted the largest comprehensive literature review assessing oncologic safety in OBCS.…”
Section: Discussionsupporting
confidence: 39%
“…To reduce the risk of LR, it is important to treat positive margins either by re-excision or mastectomy. 56 The RR rate in our study was 9.8%. This is comparable with the rate of re-excision reported by de la Cruz et al who conducted the largest comprehensive literature review assessing oncologic safety in OBCS.…”
Section: Discussionsupporting
confidence: 39%
“…Although absence of tumor at the inked margin is the current recommendation from clinical consensus guidelines, there has been a considerable variation in practice patterns among surgeons regarding the decision to re-excise or postoperative radiotherapy based on margin distance. 6 For carotid artery invasion in patients with head and neck cancer, the overall and disease-free survival rates for patients with tumors >1.8 mm from the elastic lamina were better than for patients with tumors <1.8 mm from the elastic lamina. 7 Therefore, in this study, ICA invasion needed to meet the following 2 conditions: enhanced magnetic resonance imaging (MRI) showed that the distance between the ICA and the tumor was <2 mm; and enhanced computed tomography (CT) showed that the ICA was not separated from the tumor by a thin bony wall, for example, the posterolateral wall of the sphenoid sinus.…”
Section: Patient Demographicsmentioning
confidence: 88%
“…GTR is independently associated with survival in patients with malignant tumor. Although absence of tumor at the inked margin is the current recommendation from clinical consensus guidelines, there has been a considerable variation in practice patterns among surgeons regarding the decision to re-excise or postoperative radiotherapy based on margin distance 6 . For carotid artery invasion in patients with head and neck cancer, the overall and disease-free survival rates for patients with tumors >1.8 mm from the elastic lamina were better than for patients with tumors <1.8 mm from the elastic lamina 7 .…”
Section: Methodsmentioning
confidence: 99%
“…The principal risk associated with BCS is local recurrence ranging between 0.6% and 1.5% per year (10), most of which occurs in close proximity to the tumor bed (TB) (11,12). Accurate delineation of the TB and clinical target volume (CTV) is therefore important (13,14).…”
Section: Purposementioning
confidence: 99%